ASSESSMENT OF CHARGE BEHAVIOR ACCOMPANIED WITH ELECTRICAL TREEING BY SEQUENTIALLY OBSERVED PARTIAL DISCHARGE WAVEFORMS - Abdul Matin, Totoh
Epoxy resin is a solid insulating material that is widely used in various electrical equipment. One of the main causes of electrical insulation damage to epoxy resin is an electrical tree that can erode insulating material. The electrical tree is caused by partial discharge (PD) activity. This PD activity inside tree channel can be described by charge behavior such as the movement of electrons/positive ions related to a process of electron avalanches. Previous studies have evaluated the addition effect of micro-silica filler to the insulation performance of the epoxy resin. These studies state that micro-silica fillers can improve insulation performance by reducing the activity of electrical trees. However, these studies have not yet explained why electrical tree activity can decrease. To evaluate the causes of the decrease in this electrical tree activity, the PD activity and its charge behavior need to be evaluated. In order to carry out this evaluation, our research proposes an assessment method for PD activity and its charge behavior by observing individual partial discharge waveforms sequentially. There are three experimental setup steps for this research: sample preparation, forming of electrical tree, and partial discharge measurement. Furthermore, there are two types of samples used: epoxy resin without filler and with micro-silica filler. Using the PD measurement circuit made, the individual PD waveform parameters such as waveform shapes, PD types, number of PDs, and charge amounts were collected and compared. In order to confirm the partial discharge waveform obtained, a comparison of the PD measurement results was performed on several types of PD sensors. For the result, it was found that the decrease in electrical tree activity in the silica filler sample can be caused by several reasons such as reduced number of PD occurring, decreasing effect of material degradation due to decreasing of local electrical field, and the division of energy in one PD event into smaller energy contained in several electron avalanches.